Calcium-Sensing Receptors Control CYP27B1-Luciferase Expression: Transcriptional and Posttranscriptional Mechanisms - Huang, Alice; Binmahfouz, Lenah; Hancock, Dale P; Anderson, Paul H; Ward, Donald T; Conigrave, Arthur D (Journal of the Endocrine Society, 2021)
25-hydroxyvitamin D 1α-hydroxylase (encoded by CYP27B1), which catalyzes the synthesis of 1,25-dihydroxyvitamin D3, is subject to negative or positive modulation by extracellular Ca2+ (Ca2+o) depending on the tissue. However, the Ca2+ sensors and underlying mechanisms are unidentified. We tested whether calcium-sensing receptors (CaSRs) mediate Ca2+o-dependent control of 1α-hydroxylase using HEK-293 cells stably expressing the CaSR (HEK-CaSR cells). In HEK-CaSR cells, but not control HEK-293 cells, cotransfected with reporter genes for CYP27B1-Photinus pyralis (firefly) luciferase and control Renilla luciferase, an increase in Ca2+o from 0.5mM to 3.0mM induced a 2- to 3-fold increase in firefly luciferase activity as well as mRNA and protein levels. Surprisingly, firefly luciferase was specifically suppressed at Ca2+o ≥ 5.0mM, demonstrating biphasic Ca2+o control. Both phases were mediated by CaSRs as revealed by positive and negative modulators. However, Ca2+o induced simple monotonic increases in firefly luciferase and endogenous CYP27B1 mRNA levels, indicating that the inhibitory effect of high Ca2+o was posttranscriptional. Studies with inhibitors and the CaSR C-terminal mutant T888A identified roles for protein kinase C (PKC), phosphorylation of T888, and extracellular regulated protein kinase (ERK)1/2 in high Ca2+o-dependent suppression of firefly luciferase. Blockade of both PKC and ERK1/2 abolished Ca2+o-stimulated firefly luciferase, demonstrating that either PKC or ERK1/2 is sufficient to stimulate the CYP27B1 promoter. A key CCAAT box (−74 bp to −68 bp), which is regulated downstream of PKC and ERK1/2, was required for both basal transcription and Ca2+o-mediated transcriptional upregulation. The CaSR mediates Ca2+o-dependent transcriptional upregulation of 1α-hydroxylase and an additional CaSR-mediated mechanism is identified by which Ca2+o can promote luciferase and possibly 1α-hydroxylase breakdown.